Production Cost Modeling and Simulation in the Glove Manufacturing Industry - N., Agus Salim; M. F. F., Ab Rashid (Penerbit UMP, 2023)
Product costing is an essential aspect of business strategy as it allows companies to forecast a product's future revenues and expenses and make informed decisions about its development and production. One of the main challenges in the manufacturing sector is the difficulty in selecting the optimal production setup. This can be due to changes in the product or component during the manufacturing process, leading to difficultiesin defining the best production quantity and forecasting production costs. Low productivity is another challenge faced by industrial organizations, which can affect their profitability. A case study was conducted in the glove manufacturing industry. The main objective of this research is to model the production cost for the selected case study. Cost modeling in the manufacturing industry involves creating a representation or simulation of a manufacturing process to estimate the costs associated with producing a product. Developing a cost model for the manufacturing industry involves collecting data from the industry and existing literature; developing a cost model with several function modules based on the data; validating the model by comparing its estimates to actual costs; and using the model for cost estimation, budgeting, and product pricing while keeping it updated and calibrated regularly to ensure its accuracy over time. Based on simulation analysis, productivity was improved by 4.0% compared to the original layout. In addition, the production cost per box was reduced by 4.2%. The results from this research can help companies to manage their resources and improve their profitability more effectively.